HUBUNGAN ANTARA POSITIF KADAR TIMBAL DARAH DENGAN HASIL HITUNG RETIKULOSIT PEKERJA CAT OPLOSAN - Diah Lestari; Husjain Djajaningrat (Asosiasi Institusi Pendidikan Tinggi Teknologi Laboratorium Medik Indonesia, 2021)
Level of lead in blood represent level of lead in body. Increasinglead in blood cause increasing amount of reticulocyte. Hematoxic can be used to increase awareness through effect of lead content in society for example mixed-paint workers. The purpose of this study was to determine the closeness and relation between blood lead levels and reticulocyte count results of mixed-paint workers in East Jakarta. The research an observational analytic method, cross-sectional design approach, by non-probability consecutive sampling. The results of the study, the Oplosan Paint Workers in East Jakarta region obtained high blood lead level of 0.45 mg / L, with the highest reticulocyte 1.62%. The number of Oplosan workers with lead levels exceeds the reference limit (> 0.40 mg/L) with the percentage of reticulocytes above normal (> 1.5%) of 10%. Oplosan paint workers with lead levels in the reference limit with the percentage of normal reticulocytes is still large at 80%. In conclusion, there is a significant relation between blood lead levels and the percentage of reticulocytes in mixed-paint workers in the East Jakarta area (p-value = 0,000) and shows a strong relationship with the direction of a positive relation value of r = 0.663. The close relationship with positive direction means that higher blood lead levels can shorten the life and maturation of erythrocytes with an increase in reticulocyte count.